Our National Heroes: Music and Collective Remembering - Jurková, Zuzana (Lidé města, 2018)
The following text is focused on the rise of a new, post-revolutionary (after the 1989 “Velvet Revolution”) pantheon on the Prague music scene. Two distinct modalities are discussed: a “state-supported” one, represented by the opera Toufar (the title hero of which is a priest-martyr of the Communist regime), and a subversive one, represented by the musical Velvet Havel! The ethnographic descriptions show both similarities in the music forms and languages, and a distinctiveness regarding the stakeholders. Through interviews with the authors of the presented works, the driving forces behind the rise of music representations are revealed, and the basic premises of contemporary collective memory studies about its constructed nature and about its collective-identity-forming character are confirmed.